The status of the human embryo in the context of the patentability of biotechnological inventions - Bressa, Karolina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
This article presents an overview of the issues surrounding the patenting of inventions concerning the use of the human body, the status of the human embryo and the admissibility of patenting human embryos. In his analysis, the author refers to the provisions of directive 98/44/EC of the European Parliament and of the Council from the 6th July 1998 on the legal protection of biotechnological inventions, which is the main European Union legal act on patenting biological material. Issues discussed in this article refer to article 5 of the above-mentioned directive, according to which the human body, at the various stages of its formation and development, cannot constitute a patentable invention.